The role of natural and human resources on economic growth and regional development: With discussion of open innovation dynamics - Haeruddin Saleh; Batara Surya; Despry Nur Annisa Ahmad; Darmawati Manda (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Regional economic growth is closely related to the optimization of the use of natural and human resources. This study aims to analyze: (1) The use of natural and human resource potential works as a determinant of the economic growth of Bulukumba Regency; (2) The influence of natural resources, human resources, community culture and regulation on economic growth in Bulukumba Regency. The research method used is a combination of mixed models, namely a combination of quantitative and qualitative approaches. Data was obtained through observation, survey and documentation. The results of the study show that optimizing the use of natural resources without human resource development causes its contribution to economic growth in Bulukumba Regency to be quite low which becomes an obstacle to the acceleration of economic development. The influence of natural resources, human resources, and community culture together has a significant effect on economic growth in Bulukumba Regency with a coefficient of determination 47.2%. This study recommends optimizing resource potential and strengthening human resource capacity through the use of technology and changes in community culture, which will encourage economic growth in Bulukumba Regency, South Sulawesi Province, Indonesia.
Keywords: 650; economic growth; natural resources; human resources; utilization of technology